2009
DOI: 10.1097/tp.0b013e3181963371
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate and Sirolimus as Calcineurin Inhibitor-Free Immunosuppression Improves Renal Function Better Than Calcineurin Inhibitor-Reduction in Late Cardiac Transplant Recipients With Chronic Renal Failure

Abstract: Conversion toward a CNI-free immunosuppression (Mycophenolate, sirolimus) is superior to CNI-reduced immunosuppression in improving renal failure in late HTx-recipients. However, this benefit is relativized by the increased incidence and severity of sirolimus/MMF-associated side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 26 publications
6
56
3
1
Order By: Relevance
“…At one year, GFR improved only in the CNI withdrawal group (baseline to 12 months change of 36 to 55 ml/ min versus 41 to 40 ml/min in the CNI dose reduction group). Six patients on low dose CNI (versus none off CNI) progressed to dialysis [36]. Lower baseline GFR did not predict poorer response as in other studies.…”
mentioning
confidence: 47%
See 2 more Smart Citations
“…At one year, GFR improved only in the CNI withdrawal group (baseline to 12 months change of 36 to 55 ml/ min versus 41 to 40 ml/min in the CNI dose reduction group). Six patients on low dose CNI (versus none off CNI) progressed to dialysis [36]. Lower baseline GFR did not predict poorer response as in other studies.…”
mentioning
confidence: 47%
“…More recently, VENINAHTx, a randomized study enrolled 63 late OHT patients with CKD (GFR between 15 and 60 mL/min) [36]. CNI was stopped in 30 patients and was replaced with SRL.…”
Section: Discontinuation Of Cnismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CNI-free immunosuppression after cardiac transplantation using MMF and the mTORi, sirolimus, showed a good clinical course in the absence of acute rejection in a patient with impaired renal function. 9 In Japan, the mTORi, everolimus, is already approved for use after HTx. However, as mTORi have several side effects, such as impairment of wound healing, hypercholesterolemia, inhibition of sperm production and so on, we did not chose everolimus as the first choice after pediatric HTx.…”
Section: Discussionmentioning
confidence: 99%
“…Different trials have shown that sirolimus conversion can preserve 15,35 or reverse 36,37,38,39 renal function in other organ transplanted patients receiving CNIbased immunosuppression. These studies found sirolimus as a useful alternative immunosuppressant, allowing CNI withdrawal in transplant recipients with renal impairment.…”
Section: Sirolimus Conversion In Organ Transplantmentioning
confidence: 99%